Are Pain Beliefs, Cognitions, and Behaviors Influenced by Race, Ethnicity, and Culture in Patients with Chronic Musculoskeletal Pain: A Systematic Review - Orhan, Ceren; Van Looveren, Eveline; Cagnie, Barbara; Mukhtar, Naziru Bashir; Lenoir, Dorine; Meeus, Mira (Pain physician, 2018)
Chronic pain has been considered as a biopsychosocial condition in which cognitive and emotional factors as well as biological factors significantly affect perception of pain. Race, ethnicity and culture have a crucial impact on illness beliefs, health care preferences, help-seeking behaviors, and acceptance of medical interventions. The aim of the present study was to systematically review the current evidence regarding the racial, ethnic and cultural alterations and differences in pain beliefs, cognitions, and behaviors in patients with chronic musculoskeletal pain (MSKP). Systematic review. This systematic review was conducted and reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analyses guidelines (PRISMA). PubMed and Web of Science were searched. A first screening was conducted based on title and abstract of the articles. In the second screening, full-texts of the remaining articles were evaluated for the fulfilment of the inclusion criteria. The risk of bias was assessed with the modified Newcastle-Ottawa Scale. A total of 11 articles were included. The methodological quality of the included studies ranged from low to moderate. There is moderate evidence that African-Americans use more praying, hoping, and emotion-focused coping strategies than Caucasians. There is also preliminary evidence regarding the differences in some coping strategies such as distraction, catastrophizing, and problem-focused solving between African-Americans and Caucasians. Preliminary evidence exists regarding the differences in pain coping strategies between the US and Portugal; the US and Singapore; and among 4 French-speaking countries. It is found that Spanish patients with fibromyalgia (FM) have more negative illness perceptions than Dutch patients. There is preliminary evidence that Caucasians have higher self-efficacy than African-Americans. There is also preliminary evidence that New Zealanders have more internal health expectancies than patients from the US. Preliminary evidence is demonstrated that Caucasians with rheumatoid arthritis (RA) have more positive control beliefs than African-Americans. Lastly, there is preliminary evidence that patients from the US believe that they are more disabled, while Singaporeans interpret the pain more by a traditional biomedical perspective. Only 11 articles were included. The small number of articles, wide range of assessment methods, and substantial risk of bias in the included studies led the investigator to draw conclusions cautiously. Preliminary to moderate evidence shows the differences in coping strategies, illness perceptions, self-efficacy, fear avoidance beliefs, locus of control, and pain attitudes in different populations. Further prospective and longitudinal studies using standard definitions for race, ethnicity or culture and valid questionnaires for each population are warranted to explore the racial, ethnic and cultural discrepancies in pain beliefs, cognitions, and behaviours. Chronic pain, musculoskeletal pain, pain beliefs, pain cognitions, pain behaviors, race, ethnicity, culture.